2019
DOI: 10.1508/cytologia.84.199
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Evolution Based on Variation in Chromosome Number and Chiasma Frequency in the Genus <i>Ocimum</i> L. from Thailand

Abstract: Basil, Ocimum L., is an economically important member of the family Lamiaceae. It has been widely used for many purposes, such as culinary herbs. The genus harbors large variation in chromosome number and size, which is believed to be a consequence of centuries of cultivation and selection for desirable traits. Meiosis was examined in five Ocimum species from Thailand, from five populations of each species. The results revealed that three of these species are cytogenetically related, forming a polyploid series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Ramsey and Schemske (2002) reported that induced autopolyploid species showed higher bivalent (low frequency of chiasmata) and lower multivalent (high frequency of chiasmata) pairing than expected. The reduction in meiotic recombination represented a high percentage of bivalents (diploid-like behavior) and a low percentage of multivalents were observed in several genera with polyploid series, including Senecio (Asteraceae), Bulbosus (Poaceae), and Ocimum (Lamiaceae) (Sieber and Murray 1980, Lopez et al 2005, Lopez et al 2013, Lekhapan et al 2019. This diploid-like mechanism decreases irregular meiotic behavior to produce viable gametes and increases pollen fertility, as observed in genus Senecio.…”
Section: Ploidy Level Variation and Mechanism Of Polyploid Formationmentioning
confidence: 81%
See 1 more Smart Citation
“…Ramsey and Schemske (2002) reported that induced autopolyploid species showed higher bivalent (low frequency of chiasmata) and lower multivalent (high frequency of chiasmata) pairing than expected. The reduction in meiotic recombination represented a high percentage of bivalents (diploid-like behavior) and a low percentage of multivalents were observed in several genera with polyploid series, including Senecio (Asteraceae), Bulbosus (Poaceae), and Ocimum (Lamiaceae) (Sieber and Murray 1980, Lopez et al 2005, Lopez et al 2013, Lekhapan et al 2019. This diploid-like mechanism decreases irregular meiotic behavior to produce viable gametes and increases pollen fertility, as observed in genus Senecio.…”
Section: Ploidy Level Variation and Mechanism Of Polyploid Formationmentioning
confidence: 81%
“…In addition to translocation, inversion and/or transposition were hypothetically proposed in chromosome evolution in the South American and European species of Hypochaeris (Cerbah et al 1998, Weiss-Schneeweiss et al 2003, 2008 and genus Lactuca (El-Esawi and Sammour 2014), leading to karyotypic polymorphism within/among populations. Variations in karyotype formula and/or satellite position were also observed in other plant taxa, such as genus Crotalaria (Fabaceae), genus Fragaria (Rosaceae), and genus Ocimum (Lamiaceae) (Nathewet et al 2010, Tapia-Pastrana et al 2018, Lekhapan et al 2019.…”
Section: Satellite Chromosome Variationmentioning
confidence: 85%
“…Abnormal sperm had either an aneuploid or a polyploid due to poor homolog separation at anaphase-1. In the same context, the authors [43,22,44,45,46,[47][48][49][50] proved the infertile effect of the cytogenotoxicity of two aqueous extracts.…”
Section: Discussionmentioning
confidence: 99%